2016
DOI: 10.1017/aee.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Telling Reflections: Teaching Sustainably in a Complex Learning Environment

Abstract: This article examines learning design in a postgraduate preservice teacher setting. The overarching aim was to embed environmentally responsive approaches throughout two companion units for diverse student cohorts. This article reports on a teacher educator self-study in a regional university with extensive online delivery for large units (300-800 students) in a 1-year course. The author examines how assessment tasks in literacy-and numeracy-oriented units are designed to meaningfully integrate environmental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Third-order learning is what is commonly defined as transformative and as learning for sustainability. Unsurprisingly, all of the ten publications reported learning of the first order such as raised student awareness about consumption, waste and recycling (America 2014), enhanced knowledge about local species (Jagger, Sperling, and Inwood 2016) and understanding about teaching principles (Prescott 2016), ecoliteracy and experiential learning (Burke and Cutter-Mackenzie 2010). Four studies (America 2014;Preston 2011;Burke and Cutter-Mackenzie 2010;Collins-Figueroa 2012;Preston and Griffiths 2004) additionally reported second order learning.…”
Section: What Is the Impact Of Sustainability Pedagogies On Student Teacher Learning For Sustainability?mentioning
confidence: 99%
“…Third-order learning is what is commonly defined as transformative and as learning for sustainability. Unsurprisingly, all of the ten publications reported learning of the first order such as raised student awareness about consumption, waste and recycling (America 2014), enhanced knowledge about local species (Jagger, Sperling, and Inwood 2016) and understanding about teaching principles (Prescott 2016), ecoliteracy and experiential learning (Burke and Cutter-Mackenzie 2010). Four studies (America 2014;Preston 2011;Burke and Cutter-Mackenzie 2010;Collins-Figueroa 2012;Preston and Griffiths 2004) additionally reported second order learning.…”
Section: What Is the Impact Of Sustainability Pedagogies On Student Teacher Learning For Sustainability?mentioning
confidence: 99%
“…The above results can also be attributed to various other reasons. For example, curricula are characterized by a lack of interdependence and coherence, as many scientific concepts are very general and unrelated to environmental phenomena (Prescott, 2016). As a result, students do not acquire functional knowledge in school, i.e., knowledge that helps them understand the problems of daily life (Littledyke, 2004; Perkins & Salomon, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…However, a study of more than 25,000 citizens from 27 countries concluded that despite coordinated awareness programs directed at citizens of these countries over the past 30 years to protect biodiversity, 65% of respondents did not know what was meant (Navarro-Perrez & Titball, 2012). In addition, research (Prescott, 2016) shows that school curricula are characterized by the organization of school knowledge into individual school subjects. This traditional approach leads to fragmented and abstract school knowledge that makes it difficult for children to perceive the world as a system in order to develop a more ecologically sustainable worldview.…”
Section: Ecological Knowledge and Attitudes Toward Environmental Prot...mentioning
confidence: 99%